Matthew’s perspective on Roman political authority - Repschinski, Boris (Matthew, Paul, and others, 2019)
In recent years, attempts have been made to view the gospel of Matthew through the lens of post-colonial studies as a text of resistance against a supposedly evil Roman empire. This study evaluates the approaches of Matthew Carter, David Sim, and Dorothy Jean Weaver. It judges the approaches of Carter and Sim as unsatisfactory in the light of the way Matthew’s gospel keeps a distance between Roman imperial imagery and the image of the kingdom of heavens while at the same time avoiding any notion of an eschatological reckoning with Roman imperial power. While the gospel has little positive to say about Roman authority, it is lumped together with other political entities in a generalizing fashion to establish the kingdom of heavens as a counter sign.